Weighted Grand Herz-Type Spaces and Its Applications. (23rd November 2022) - Yu, Xia; Liu, Zongguang
Abstract : In this paper, we introduce the weighted grand Herz spaces and weighted grand Herz-type Hardy spaces. The decompositional characterizations of these spaces are established. As its applications, the boundedness of some sublinear operators are established.